Economic action in theory and practice anthropological investigations - Wood, Donald C. (Research in economic anthropology, 2010)
This volume contains 14 original chapters focusing on various aspects of economic organization and behaviour, mostly based on empirical fieldwork conducted by the authors themselves. It is a well-balanced collection of chapters on economic issues studied anthropologically, not only in its geographical and theoretical focus but also in showcasing work by established and emerging researchers. Chapters on Africa take a close look at urban food provisioning in Cameroon and an investigation into entrepreneurial activities in the rapidly-changing economy of Cairo. Other chapters examine places and cultures in Central Asia - property rights and state power in Kazakhstan, and animal markets in Kashgar, Western China. The buying and selling activities of ethnic groups within larger societies such as Latin Americans in the USA and Gabor Roma in Romania are highlighted. Concerning North America are chapters on the trans-Atlantic (and global) art market, and on oil drilling in Canada, while in Latin America, income disparities and inequalities in Brazil, development in Colombia, and kin-like compadrazgo networks in Mexico are analyzed. Historical Western Europe and pre-historical Ecuador are also covered.